Strategi Komunikasi Kampanye Komunitas Jurnalisme Berkebangsaan Upaya Mempertahankan Partisipasi di Kompas Gramedia - Pandyangqa, Nuno Pereira Vidya; Heriyanti, Heriyanti; Wiryany, Detya; Larasati, Ayu (Green Publisher Indonesia, 2025)
This study examines the campaign communication strategy of the National Journalism Community at Kompas Gramedia to maintain member participation, with a focus on the application of Social Cognitive Theory (Bandura, 1986) and supporting theories on communication strategy, campaigns, and communities. The study uses a constructivist paradigm and qualitative methods through in-depth interviews, observations, and document analysis. The results show that the campaign communication strategy includes planning (audience research and narratives), communication (visual content on social media and educational sessions), implementation (activities such as Tiba Bersua and clean-up actions), and evaluation (feedback and). Personal factors (knowledge, emotions, self-efficacy), environmental (collaborative culture, mutual cooperation values), and behavioral (concrete actions, feedback) interact to encourage participation. However, barriers such as the perception of activities as a burden, narratives that are less relevant to Gen Z, technical constraints, lack of initial guidance, and irregular feedback reduce effectiveness. Solutions implemented include flexible scheduling, engaging visual content, and intensive mentoring. This study enriches communication theory and provides practical guidance for increasing community participation through structured and responsive communication strategies.